Evaluation of Clinical Distribution and Antimicrobial Resistance of Klebsiella pneumoniae - Xie, Liping; Wu, Zhen’an; Wei, Na; Zhang, Liang; Tang, Jiajian; Wang, Hongmei (Current Pharmaceutical Analysis, 2024)
PurposeThis paper aims to analyze the clinical distribution and drug resistance changes of Klebsiella pneumoniae (KPN) from 2017 to 2021 in the Beijing Hospital of Integrated Traditional Chinese and Western Medicine to provide a reference for the clinical rational use of antibiotics.MethodsWe collected Klebsiella pneumoniae isolated from various clinical specimens in 2017-2021, analyzed the isolation rate, specimen distribution, and department distribution characteristics during the five years, and statistically analyzed their drug sensitivity tests and multiple drug resistance. Zhuhai Deere DL-96 full-automatic microbial analyzer was used for bacterial identification and drug sensitivity tests. The drug sensitivity test was interpreted according to the standards recommended by the American Clinical and Laboratory Standards Institute (CLSI).ResultsA total of 1057 strains of Klebsiella pneumoniae were identified between 2017 and 2021, with proportions of 18.6%, 15.7%, 15.4%, 15.1%, and 15.0% in each respective year. Specimen distribution included sputum (66.0%), urine (17.9%), throat swab (9.4%), secretion (2.4%), pus (0.7%), venous blood (0.6%), vaginal swab (0.4%), and other sources (2.6%). Distribution by the department revealed specimens originating from the respiratory department (21.2%), cardiology department (17.8%), neurology department (13.4%), oncology department (13.0%), nephrology department (12.2%), acupuncture department (10.1%), and other departments (12.3%). In terms of drug susceptibility testing, Klebsiella pneumoniae exhibited high resistance rates to ceftriaxone, cefotaxime, ceftazidime, and ampicillin/sulbactam, with rates of 50.8%, 46.8%, 46.3%, and 43.6% respectively. Conversely, resistance rates to minocycline, amikacin, imipenem, and meropenem were relatively low, at 8.6%, 16.5%, 8.5%, and 9.4% respectively. Resistance rates to cefepime/sulbactam and piperacillin/tazobactam were 29.9% and 28.9%, respectively, while cephalosporin resistance rates ranged from 36.1% to 50.8%. Regarding multidrug resistance, the detection rates of ESBL-producing Klebsiella pneumoniae were 8.2%, 10.9%, 4.5%, 10.6%, and 6.4% from 2017 to 2021, with an average detection rate of 7.9%. The detection rates of CR-Kp were 12.1%, 11.7%, 5.8%, 9.9%, and 8.9% respectively, averaging 9.6% over the five-year period.ConclusionThe sputum specimen of Klebsiella pneumoniae exhibits the highest detection rate among specimen distributions, signifying its significance as a pathogenic bacterium in respiratory tract infections. Notably, the respiratory department demonstrates the highest detection rate, underscoring the necessity to enhance the monitoring and management of Klebsiella pneumoniae infections in respiratory patients. Over the past five years, our hospital has observed a decreasing trend in the overall drug resistance rate of Klebsiella pneumoniae to 17 antibiotics. While imipenem and meropenem exhibit minimal resistance rates, these carbapenem antibiotics serve as crucial agents for treating gram-negative bacilli, particularly in critically ill patients, and are thus not recommended as first-line choices for routine clinical use. Conversely, minocycline, amikacin, ceftazidime/sulbactam, and piperacillin/tazobactam showcase relatively low resistance rates, enabling their empirical use based on clinical experience. Combination therapy with other antibiotics is advised for amikacin. Conclusion: Nevertheless, cephalosporins display a relatively high resistance rate, necessitating a reduction in their clinical utilization. Regarding multidrug resistance, the detection of ESBLs-producing Klebsiella pneumoniae (KP) and Carbapenem-Resistant KP (CR-Kp) has exhibited a declining trend over the past three years. Despite this positive trend, the issue of multidrug resistance in Klebsiella pneumoniae remains severe, with instances of complete drug resistance reported. Clinicians are urged to judiciously administer antibiotics guided by drug sensitivity test results and resistance rate variations, restrict the use of broad-spectrum antibiotics, and manage the emergence and spread of ESBLs-producing and CR-Kp bacteria.
Keywords: drug resistance